Trend and Distribution of Refractive Errors Among Children Attending a Private Optometry Practice in Northern Malaysia - Nadiah Rashidi; Abdul Rahim, Muhammad Afzam Shah; Yusof, Firdaus (International Journal of Allied Health Sciences, 2025)
Background: Childhood myopia is escalating worldwide, increasing lifetime risks of ocular diseases and affecting educational and psychosocial outcomes. In Malaysia, practice-based evidence from private optometry is limited, constraining planning for screening and myopia-control services. Objective: To determine the prevalence and age-related distribution of myopia and other refractive errors among children attending a private optometry practice in northern Malaysia, and to examine associations with age and gender. Methods: This retrospective, cross-sectional review of electronic health records for 700 first-visit pediatric patients (<18 years) at a private optometry clinic in Ipoh, northern Malaysia, between April 2021 and June 2025. Refractive status was classified by spherical equivalent (SE) in the more ametropic eye as myopia (>0.50 D), high myopia (< 5.00 D), hyperopia (>+0.50 D), or emmetropia (-0.50 D < SE < +0.50 D). Age-stratified prevalence was summarized descriptively, and associations with age group and gender were tested using chi-square analysis. Results: Myopia predominated, affecting 76.4% (n=535 from 700) of children, with 10.7% (n=75/535) classified as high myopia. Hyperopia followed, affecting 14.6% (n=102/700), and emmetropia accounted for 9.0% (n=93/700). The association between age group and refractive error type was significant (p<0.001): myopia prevalence rose from 54.9% in preschoolers (5–6 years) to 73.6% (7–9), 74.4% (10–12), 86.8% (13–15), and 83.5% in upper-secondary students (16–17 years). Hyperopia declined across age groups, whereas emmetropia remained relatively stable. Myopia was slightly more frequent in males (80.1%) than in females (73.5%), while hyperopia was more frequent in females (18.3%) than in males (10.0%) (p=0.008). Conclusion: In this northern-Malaysian private-practice cohort, myopia was highly prevalent and increased sharply across school years, with nearly one in ten children exhibiting high myopia. Hyperopia predominated in early childhood, whereas emmetropia remained relatively stable. These practice-based findings support early pediatric vision screening and integration of evidence-based myopia-control strategies within community and private care pathways. Future research should include cycloplegic refraction, axial-length monitoring, and evaluation of environmental and behavioral risk factors, as well as cost-effectiveness analyses of clinic-integrated interventions in Malaysian settings.